Size-related variation in helminth infection among Oreochromis niloticus from sewage ponds in Gwale Local Government Area, Kano State, Nigeria - Abdu, Habibu Maaruf; Shah, Mohammad Manjur; Nabegu, Zainab Nura; Yuguda, Binta Abdullahi; Muhammad, Zakiyya Ibrahim (International Multidisciplinary Research Journal, 2025)
Helminth infections in freshwater fishes are a major ecological and public health concern, especially in polluted habitats such as sewage ponds where transmission risks are amplified. This study investigates the relationship between fish body size and helminth parasite infection in Oreochromis niloticus collected from sewage ponds in Gwale Local Government Area, Kano State, Nigeria. A total of 385 fish were collected and classified into four standard length groups (2-5 cm, 6-8 cm, 9-11 cm, and 12-14 cm). Parasitological examination revealed that helminth prevalence was highest in fish within the 9-11 cm group (47.01%) and lowest in the smallest size group (2-5 cm, 18.92%). Pearson’s correlation test showed a moderate positive relationship between fish length and infection prevalence (r=0.496, p<0.05), suggesting that susceptibility to helminth infection increases with size up to a threshold, beyond which prevalence declines slightly. The observed pattern may reflect complex interactions between diet breadth, cumulative exposure time, and immune development. These findings provide useful insight into host-parasite dynamics in polluted freshwater ecosystems and emphasize the need for monitoring fish health in sewage-impacted aquaculture environments, both for ecological management and to safeguard public health.